Reinforcement of sandy soil using plastic fibres made from waste plastic bottles - M. Alshkane, Younis (Iraqi Journal of Civil Engineering, 2017)
Today waste plastic bottles are spread widely throughout our world especially in Kurdistan, an autonomous region in Iraq. These waste products cause many environmental problems and at the same time some soils are weak and need reinforcement using cheap materials such as Polyethylene terephthalate (PET) waste plastic bottle. Use of waste plastic bottles as a reinforcement of soil is highly recommended to reduce the amounts of plastic waste, which creates a disposal problem. In this study an attempt was made to use plastic fibres produced from waste bottles to reinforce sandy soil. This can solve both environmental and geotechnical problems. In the research, the effect of plastic fibres content as well as fibre length on shear strength parameters (cohesion and internal friction) were experimentally predicted using the direct shear test method so as to improve bearing capacity of weak soils. The results showed that under low normal stress the inclusion of plastic fibres increased both angle of internal friction and cohesion; however, under high normal stress (greater than 100 kPa) the cohesion increased and the internal friction was roughly unchanged. Also, it was concluded in this study that the suitable amount of fibers that can be added to weak soils is 1% of dry weight of sand.